Identification of occupational risk factors by interviewing injured workers in an out-patient clinic (Italian Journal of Public Health, 2010)
Background: To prevent injuries, identification of the involved risk factors is necessary. Two recent in-depth investigations were carried out in the health service of Oslo on workers seeking treatment of severe occupational injuries. The interviews were rather time-consuming, and hence rather costly. The aim of thepresent study was to find a less time-consuming method which nevertheless would identify preventable risk actors.Methods: In-depth investigations of 15 injuries with nail guns and 28 injuries related to scaffolding were onducted in an out-patient clinic in Trondheim, Norway. Patients were interviewed by health personnel just efore or after the treatment based on specifically designed questionnaires. A group of specialists analysed the information collected.Results: Some risk factors were identified: design weaknesses inherent in nail guns, presence of snow and ice at the injury location, foreign body in the eye and lack of control/inspection of scaffolding when erected. On average, about two man hours were used for each injury. The most relevant questions were those directly related to the narrative, in particular how the injury occurred, and if any special conditions were involved. Quite a few data elements require epidemiological representative studies in order to assess them as potential risk factors.Conclusions: This relatively low time-consuming method revealed some risk factors. However, it could be more effective if the interviews were conducted by telephone a few days after the treatment by a specialist in that particular injury type; such as an experienced labour inspector, in order to probe more deeply into the technical risk factors.
Keywords: In-depth investigation; occupational risk factors; nail gun; scaffoldings